IMPLEMENTASI PENGUATAN MODERASI BERAGAMA DI SEKOLAH TINGGI AGAMA BUDDHA NEGERI RADEN WIJAYA - Tantra, Manggala Wiriya; Agus Siswadi, Gede (Lembaga Penerbit Sekolah Tinggi Hindu Dharma Klaten, 2024)
Religious extremism in universities is a real threat to national disintegration that has the potential to lead to acts of intolerance and terrorism in the name of religion. The central government is trying to mainstream religious moderation in anticipating religious exclusivism and extremism movements on campus. This study aims to describe the implementation of religious strengthening in universities, specifically at the Raden Wijaya State Buddhist College (STABN). This study uses a qualitative method with a phenomenological approach. The results of this study indicate that the strengthening of religious moderation is being carried out systematically, specifically for educators, education personnel and students. Educators and education personnel are trained to become pioneers and movers of religious moderation by national instructors and facilitators. Students are given socialization of religious moderation and are strengthened in their understanding of religious moderation through courses that integrate religious moderation in all study programs. At STABN Raden Wijaya there is also a House of Religious Moderation which functions as a program planner, program implementer and study of strengthening religious moderation.